2012
DOI: 10.1111/j.1468-5965.2012.02313.x
|View full text |Cite
|
Sign up to set email alerts
|

The Committee of the Regions and the European Economic and Social Committee: How Influential are Consultative Committees in the European Union?

Abstract: The European Economic and Social Committee (EESC) and the Committee of the Regions (CoR) are two advisory bodies of the European Union involved in a broad array of policy areas. However, little is known about the effects of the two committees on the positions of the other institutions or final policy outcomes. This article investigates to what extent and under what conditions the CoR and the EESC can exert influence. Based on a comprehensive survey conducted in 2010, a series of hypotheses derived from a neo-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…While central government helpfulness is unrelated to lobbying success directly in Brussels, CoR helpfulness only significantly increases lobbying success in Model 4 but loses significance in the more controlled setting of Model 5 and therefore should be considered with caution. This is in line with past findings, highlighting that influence via the CoR is conditioned by a number of specific factors (Hönnige and Panke ; Neshkova ).…”
Section: The Individual Contextual and Conditional Determinants Of supporting
confidence: 93%
See 1 more Smart Citation
“…While central government helpfulness is unrelated to lobbying success directly in Brussels, CoR helpfulness only significantly increases lobbying success in Model 4 but loses significance in the more controlled setting of Model 5 and therefore should be considered with caution. This is in line with past findings, highlighting that influence via the CoR is conditioned by a number of specific factors (Hönnige and Panke ; Neshkova ).…”
Section: The Individual Contextual and Conditional Determinants Of supporting
confidence: 93%
“…Finally, as it is their formal and institutionalized access point in the EU's policy‐making process, I identify the Committee of the Regions (CoR) as the third key policy ally. Indeed, recent research has found that despite disappointed expectations, the CoR has been able to influence the EU's legislative process, albeit under certain specific conditions (Hönnige and Panke ; Neshkova ).…”
Section: Regional Influence In Brussels: Contextual and Individual‐lementioning
confidence: 99%
“…Similarly, the European Economic and Social Committee, whose members come from employer and workers organizations and other organized interest groups, issues opinions on socioeconomic matters. Both Committees, however, exercise limited influence (40). Also, more than 40 specialized agencies operate in discrete areas (41).…”
Section: Eu Bodies and Member Statesmentioning
confidence: 99%
“…This illustration refers to "goal attainment" or "preference attainment." Many scholars have indeed asserted that evidence on goal or preference attainment is one of the most direct indicators of influence (Betsill & Corell, 2001;Bunea, 2013;Dür, 2008a;Hönnig & Panke, 2012;Mahoney, 2007;Panke et al, 2015). The basic idea of goal or preference attainment is that the distance between a policy outcome and the ideal point of an actor reflects the influence of this actor (Dür, 2008a;Dür et al, 2015).…”
Section: Measuring Influence Of Eu Agenciesmentioning
confidence: 99%
“…What is noteworthy to mention at this point is studies on two consultative committees in the EU -the European Economic and Social Committee (EESC) and the Committee of the Regions (CoR) -in the legislative decision-making process (see e.g., Hönnig & Panke, 2012;McCarthy, 1997;Panke, Hönnig, & Gollub, 2015). These committees share some common characteristics with EU agencies in a broad sense because they, as advisors, may be involved in the policymaking process and requested to provide opinions based on their expertise.…”
Section: Introducing Eu Agenciesmentioning
confidence: 99%